ART FILM AS A MEANS OF FORMING LINGUISTIC AND SOCIO-CULTURAL (Farabi Journal of Social Sciences, 2020)
The article reveals the knowledge of a foreign language that implies not only the ability to speak or writein a foreign language but conducting intercultural dialogue, which requires not only language, but also cultural, countrystudies and other training. Readiness for film intercultural communication is the key to success both in the professionalsphere and in the sphere of personal self-realization.Also it was focused on the most effective method of work will bea conversation about whether the expectations associated with the title of the film and the illustration on the cover weremet. The use of authentic feature films in the process of teaching a foreign language has become firmly established inthe practice of modern school and University teaching. but also more broadly - to conduct intercultural dialogue, whichrequires not only language, but also cultural, country studies and other training. The analysis of methodical literatureconfirms the expediency of using authentic feature films in the process of teaching a foreign language.